Timing of inguinal hernia following complete primary repair of bladder exstrophy. Issue 1 (February 2021) - Lee, Ted; Vasquez, Evalynn; Logvinenko, Tanya; Venna, Alyssia; Frazier, Jennifer; Lingongo, Melissa; Roth, Elizabeth; Weiss, Dana; Groth, Travis; Shukla, Aseem; Kryger, John V.; Canning, Douglas A.; et al.
Summary: Introduction/background: Bladder exstrophy patients have a high prevalence of inguinal hernia that often become clinically evident following bladder closure. Understanding when the bladder exstrophy patient is under greatest risk of developing an inguinal hernia following bladder closure is important, since incarceration resulting in strangulation of intra-abdominal contents can lead to significant morbidity if not addressed in a timely fashion. Although the incidence and risk factors of inguinal hernia have been reported, the timing of occurrence is not well understood. Objective: The primary objective of this study was to assess the timing of inguinal hernia following complete primary repair of bladder exstrophy (CPRE). In addition, we aimed to evaluate possible risk factors associated with inguinal hernia, including sex, age at bladder closure and iliac osteotomy status. Study Design: A multi-institutional retrospective review identified patients with bladder exstrophy repaired by CPRE under 6 months of age while excluding those who underwent inguinal hernia repair before or during bladder closure. Timing of inguinal hernia following bladder closure was evaluated using Kaplan–Meier methods. Cox proportional hazards model was used to investigate association of sex, age at bladder closure, and osteotomy on the risk of developing of inguinal hernia while clustering for institution. Results: 91 subjects were included in our analysis with median follow-up time of 6.5 years. 34 of 53 males (64.2%) and 2 of 38 females (5.3%) underwent inguinal hernia repair. The median time to inguinal hernia was 4.7 months following closure. The greatest hazard of inguinal hernia was within the first six months following closure. In multivariate analysis, male sex was strongly associated with inguinal hernia (HR = 19.00, p = 0.0038). Osteotomy and delay in closure were not significantly associated with inguinal hernia. 7 of 36 patients (19.4%) who underwent inguinal hernia repair presented with recurrence on the ipsilateral side. Discussion: Our results suggest that the greatest risk of inguinal hernia is within the first six months following bladder closure. The decreased risk of inguinal hernia after one year of follow-up may reflect anatomic stability that is reached following major reconstruction of the pelvis. While male bladder exstrophy patients are significantly more susceptible to inguinal hernias following CPRE, osteotomy and delayed bladder closure do not appear to be protective factors for inguinal hernia development following initial bladder closure. Conclusions: There is a heightened risk of inguinal hernia in the first six months following closure. The rate of recurrence following inguinal hernia repair is significantly elevated compared to the general pediatric population. Summary Figure Kaplan–Meier curves for overall probability of inguinal hernia repair for males and females Summary Figure